A multicomponent psychosocial intervention to reduce substance use by adolescents involved in the criminal justice system: the RISKIT-CJS RCT - Coulton Simon; Nizalova Olena; Pellatt-Higgins Tracy; Stevens Alex; Hendrie Nadine; Marchand Catherine; Vass Rosa; Deluca Paolo; Drummond Colin; Ferguson Jennifer; Waller Gillian; Newbury-Birch Dorothy (NIHR Journals Library, 2023)
Background Substance use and offending are related in the context of other disinhibitory behaviours. Adolescents involved in the criminal justice system constitute a particularly vulnerable group, with a propensity to engage in risky behaviour that has long-term impact on their future health and well-being. Previous research of the RISKIT programme provided evidence of a potential effect in reducing substance use and risky behaviour in adolescents. Objectives To evaluate the clinical effectiveness and cost-effectiveness of a multicomponent psychosocial intervention compared with treatment as usual in reducing substance use for substance-using adolescents involved in the criminal justice system. Design A mixed-methods, prospective, pragmatic, two-arm, randomised controlled trial with follow-up at 6 and 12 months post randomisation. Setting The study was conducted across youth offending teams, pupil referral units and substance misuse teams across four areas of England (i.e. South East, London, North West, North East). Participants Adolescents aged between 13 and 17 years (inclusive), recruited between September 2017 and June 2020. Interventions Participants were randomised to treatment as usual or to treatment as usual in addition to the RISKIT-Criminal Justice System (RISKIT-CJS) programme. The RISKIT-CJS programme was a multicomponent intervention and consisted of two individual motivational interviews with a trained youth worker (lasting 45 minutes each) and two group sessions delivered over half a day on consecutive weeks. Main outcome measures At 12 months, we assessed per cent days abstinent from substance use over the previous 28 days. Secondary outcome measures included well-being, motivational state, situational confidence, quality of life, resource use and fidelity of interventions delivered. Results A total of 693 adolescents were assessed for eligibility, of whom 505 (73%) consented. Of these, 246 (49%) were allocated to the RISKIT-CJS intervention and 259 (51%) were allocated to treatment as usual only. At month 12, the overall follow-up rate was 57%: 55% in the RISKIT-CJS arm and 59% in the treatment-as-usual arm. At month 12, we observed an increase in per cent days abstinent from substances in both arms of the study, from 61% to 85%, but there was no evidence that the RISKIT-CJS intervention was superior to treatment as usual. A similar pattern was observed for secondary outcomes. The RISKIT-CJS intervention was not found to be any more cost-effective than treatment as usual. The qualitative research indicated that young people were positive about learning new skills and acquiring new knowledge. Although stakeholders considered the intervention worthwhile, they expressed concern that it came too late for the target population. Limitations Our original aim to collect data on offences was thwarted by the onset of the COVID-19 pandemic, and this affected both the statistical and economic analyses. Although 214 (87%) of the 246 participants allocated to the RISKIT-CJS intervention attended at least one individual face-to-face session, 98 (40%) attended a group session and only 47 (19%) attended all elements of the intervention. Conclusions The RISKIT-CJS intervention was no more clinically effective or cost-effective than treatment as usual in reducing substance use among adolescents involved in the criminal justice system. Future research The RISKIT-CJS intervention was considered more acceptable, and adherence was higher, in pupil referral units and substance misuse teams than in youth offending teams. Stakeholders in youth offending teams thought that the intervention was too late in the trajectory for their population. Trial registration This trial is registered as ISRCTN77037777. Funding This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 11, No. 3. See the NIHR Journals Library website for further project information. Plain language summary We explored how useful a psychological intervention was in reducing substance use among young people who had some involvement in the criminal justice system. We recruited young people aged between 13 and 17 years in four areas of England (i.e. South East, London, North West and North East). Young people were recruited from youth offending teams, pupil referral units and substance misuse teams. Those young people who were willing to participate were offered usual treatment and half, chosen at random, were offered an opportunity to take part in the RISKIT-Criminal Justice System (RISKIT-CJS) programme. The RISKIT-CJS programme had four distinct parts. The first was a 1-hour session that used an approach called motivational interviewing to explore the young person's substance use and discuss different strategies to change their behaviour. This was followed by two group sessions delivered over 2 consecutive weeks. These group sessions addressed risks associated with substance use, what triggers use and the health and social consequences. In addition, young people were taught new skills to help them manage in situations in which they might normally use substances. At the end of the group sessions, the young people had another motivational interview. Twelve months after participants started, we found that the frequency of substance use had decreased in both groups; however, the RISKIT-CJS intervention was no better than treatment as usual. When we spoke with young people who had taken part and staff involved with this population, we got a mixed picture. In some settings, particularly pupil referral units, the RISKIT-CJS intervention was well received by young people and staff, and staff felt that it was a useful additional resource to the work that they were currently undertaking. On the other hand, in the youth offending teams, the staff thought that the programme was too different from their normal work to be implemented easily and they considered the population they work with too established in their substance use and criminal activity to benefit from the programme. Scientific summary Background Adolescence is a critical developmental stage when young people make behavioural and lifestyle choices that have the potential to affect their health and well-being into adulthood. Six per cent of youths aged 14 years and 11% of youths aged 15 years report having used cannabis in the last month, with 2% of 14-year-olds and 4% of 15-year-olds reporting use of a class A substance at least once. Data from the Juvenile Cohort Study [Wilson E. Youth Justice Interventions - Findings from the Juvenile Cohort Study (JCS). London: Ministry of Justice Analytical Series; 2013] show that 32% of young offenders indicate substance use is, at least in part, a reason for them associating in criminal activity. Substance use is defined as the use of alcohol, traditional illicit substances and legal highs, as well as inappropriate use of prescribed medication. Although the relationship between substance use and criminal activity is complex, it is clearly a major issue in the youth offending population. To date, systematic reviews of interventions for substance-using offenders in criminal justice system (CJS) environments have not identified a clear evidence-based intervention strategy. Systematic reviews have revealed the paucity of good-quality research in the area and a lack of UK-based studies, with no scientifically rigorous studies focusing on young offenders. Importantly, previous research has identified what has been proven not to work, and this includes focusing on negative aspects of risk and risk abstinence. Promising intervention approaches identified include motivational interviewing and cognitive and socioemotional life skills training. In addition, there is emerging recognition of the importance of providing interventions in a structured manner and, with the young people's preference for peer group interventions, the importance of managing the potentially negative effects of labelling and peer influence. The RISKIT-Criminal Justice System (RISKIT-CJS) programme is a structured psychosocial intervention developed from evidence reviews and co-production with young people. Pilot research work among risk-taking adolescents in school settings found that the intervention was acceptable and associated with significant reductions in substance use.